The relationship between sense of coherence and post-traumatic stress: a meta-analysis. Issue 1 (1st January 2019) - Schäfer, S. K.; Becker, N.; King, L.; Horsch, A.; Michael, T.
ABSTRACT: Background : Antonovsky's concept of sense of coherence (SOC) – as a global orientation reflecting an individual's feeling of confidence in both the predictability of their internal and external environment and their ability to cope with stressful and challenging situations in life – shows a negative association with symptoms of post-traumatic stress. However, single studies varying in study characteristics provide heterogeneous effect size estimations. Objective : The purpose of the current study is to investigate the relationship between SOC and post-traumatic stress disorder (PTSD) symptom severity for the first time on a meta-analytical level. Method : The random-effects meta-analysis is based on zero-order correlations ( r ) and consists of 47 independent samples out of 45 studies ( N  = 10, 883). Results : After correcting for sampling error, the mean correlation between SOC and PTSD symptoms was M ( r ) = −.41 (excluding four outliers: −.39). However, this effect could not be generalized to all types of PTSD samples owing to substantial remaining heterogeneity. Subsequent moderator analyses investigating the influence of different SOC and PTSD measures, trauma type and duration, mean age and gender imbalances per sample did not reveal significant moderating effects. Conclusions : The meta-analysis reveals a substantial correlation between SOC and PTSD symptom severity: higher SOC levels are associated with lower symptom severity. Thus, future research should progress to the question of whether the relationship between SOC and post-traumatic stress is causal, and by which factors it is moderated. Abbreviations : CD, Cook's distance; DSM, Diagnostic and Statistical Manual of Mental Disorders; (G)RR, general (and specific) resistance resources; IES(-R), Impact of Event Scale (Revised); PDS, Posttraumatic Stress Diagnostic Scale; PRISMA, Preferred Reporting Items for Systematic Reviews and Meta-Analyses; PTSD, post-traumatic stress disorder; SDR, standard deleted residual; SOC, sense of coherence; SOC-R, Sense of Coherence Scale – Revised